China's Trade‐Off Between Economic Benefits and Sulfur Dioxide Emissions in Changing Global Trade - Feng Wang; Yongyuan Li; Wei Zhang; Pan He; Ling Jiang; Beiming Cai; Jing Zhang; Pengyan Zhang; Haoran Pan; Hongqiang Jiang (Earth's Future, 2020)
Abstract China has been suffering from air quality degradation since its ascension into the World Trade Organization in 2001. The unequal exchange that occurs with international trade—that is, developed countries obtaining larger shares of trade‐related value added relative to the shares of trade‐related air pollution incurred locally—may obstruct the greening of global supply chains. In this study, we conduct a multi‐regional input‐output analysis to examine the change in the distribution of economic benefits and sulfur dioxide emissions underlying China's international trade from 2002 to 2015. The results show that both net trade‐related economic benefits and SO2 emissions in China rapidly increased from 2002 to 2007 and then decelerated after 2007 due to changes in China's green development strategy. In the past 13 years, China has suffered from economic‐environmental inequality due to trade with most developed countries, for example, the United States, the European Union, East Asia, and Canada. East Asia, particularly Japan and South Korea, became both an economic and environmental winner while trading with China in 2015. China has also outsourced emissions to less developed regions, such as Sub‐Saharan Africa. We propose policy implications to further reduce the economic‐environmental inequality underlying China's international trade.